Pyrolysis, Combustion, and Fragmentation Model of Coal Particles: Preliminary Results. Issue 4 (3rd May 2016) - Senneca, Osvalda; Urciuolo, Massimo; Bareschino, Piero; Diglio, Giuseppe; Pepe, Francesco; Chirone, Riccardo
ABSTRACT: A mathematical model has been developed to predict fragmentation of particles under a wide range of pyrolysis and combustion conditions. The model is an upgrade of a previous one that took into account only fragmentation during the heat up and devolatilization stage. The model calculates the temperature and oxygen profiles within the particle, the evolution of internal porosity as a consequence of both devolatilization and carbon combustion, the mechanical stress caused by temperature gradients, and by volatiles-generated overpressure inside the particles. Eventually the model calculates the probability of rupture of the particle based on the Weibull (1939) theory. The model has been used to simulate heating of coal particles under inert conditions at different heating rates and temperatures showing good agreement with previous work. The model has been further used to simulate heating under oxidative conditions in order to highlight the role of combustion on fragmentation phenomena.